Empowering women in chemistry via a global networking event: IUPAC Breakfast - UiTM, Fakulti Sains Gunaan (Faculty of Applied Sciences, 2019)
The School of Chemistry had organized a breakfast networking event on 12 February 2019 and connected with other groups of women chemists around the world. The event was conducted as a way of strengthening the bonds between women in chemistry. It was initiated by Prof. Datin Dr Rohaya Ahmad and Prof. Dr Nor Hadiani Ismail. The event started with a welcoming remark by the organizer and Head of School of Chemistry, followed by a sharing session. Among the speakers were Assoc. Prof. Dr Sabiha Hanim Saleh, Prof. Ts. Dr Chan Chin Han, Assoc. Prof Dr Zainiharyati Mohd Zain, Prof Dr Hadariah Bahron, Prof. Datin Dr Rohaya Ahmad, Prof. Dr Nor Hadiani Ismail and Prof Dr Norashikin Saim.